KESESUAIAN ALAT DAN MESIN UNTUK PENGUSAHAAN HUTAN TANAMAN INDUSTRI - Sri Sutopo; Djaban Tinambunan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Several short investigations have been conducted lo find the suitability of equipment and machine used in foreste estate operations. Original condition of land, soil cultivation practices, and the productivity of various equipment were also collected.The areas used for linber estate are usually alang-alang grassland with the alang-alang densitv of around two million stems/ha, the average slope of 8%, consited of red yellow to red brown podsolik soils. the soil is plowed twice hy using disc plow of 70 cm diameter with the plowing depth of 20-30 cm. and then harrowed by using disc harrow of 46 cm diameter with the harrowing depth of 15-20 cm.The efective power used for plowing is around 25 HP and for harrowing is around 19 HP. Therefore the engine power required (with 50% efficiency) is around 50 HP. For harrowing with this level of power, the harrow can be extended up 10 4.8 m wide to increase power efficiency,Felling productivities by using chainsaw and feller-buncher are 7.096 and 7. 708 m3/hour, respectivelv, The difference between these two figures is not significant. While the skidding productivities by using tractor (140 HP) and feller-buncher are 4.929 and 5.140 m3/hour, respectively, The difference between this two figures is highly significant.Tge relationship between the power of tractor and productivity is linear with higher productivity when the power is larger. Other result shows that the tractor used are mostly too large and, therefore, need the modification of plow and harrow combinations.